Task Offloading and Resource Allocation Mechanism of Moving Edge Computing in Mining Environment - Yifan Meng (IEEE, 2021)
The mine improves the response speed of the IoT control system by sinking computing services into the MEC Server. In this case, computing resources are scattered and it is difficult to cope with the changing computing requirements of mobile terminal devices. To solve this problem, we optimize from the supply side by build P.M.R (problem of maximum revenue) problem. In P.M.R, we comprehensively consider the air rate of wireless communication, network delay, computing resource demand and other factors that affect the offloading task of terminals. To obtain the relative optimal solution of P.M.R, we construct a task unloading algorithm based on particle swarm optimization. And we set up a simulation experiment environment according to the mine network parameters. The experimental results show that this task unloading algorithm can effectively improve the efficiency of computing facilities in the system and achieve load balancing.